2016
DOI: 10.1105/tpc.16.00178
|View full text |Cite
|
Sign up to set email alerts
|

FYVE1/FREE1 Interacts with the PYL4 ABA Receptor and Mediates Its Delivery to the Vacuolar Degradation Pathway

Abstract: Recently, we described the ubiquitylation of PYL4 and PYR1 by the RING E3 ubiquitin ligase RSL1 at the plasma membrane of This suggested that ubiquitylated abscisic acid (ABA) receptors might be targeted to the vacuolar degradation pathway because such ubiquitylation is usually an internalization signal for the endocytic route. Here, we show that FYVE1 (previously termed FREE1), a recently described component of the endosomal sorting complex required for transport (ESCRT) machinery, interacted with RSL1-recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 101 publications
(202 reference statements)
3
143
0
9
Order By: Relevance
“…The ELC/AtVPS23A ESCRT-I component also binds Ub in vitro (Spitzer et al, 2006). Interestingly, ELC/ AtVPS23A and AtFYVE1 directly bind to the AtPYL4 abscisic acid (ABA) receptor and AtIRT1, two ubiquitinated endocytosed cargos (Barberon et al, 2014;Belda-Palazon et al, 2016;Yu et al, 2016). Consistently, genetic interference with ELC/AtVPS23A or AtFYVE1 expression yields ubiquitinated protein accumulation in (Zhou et al, 2013), sequestration of anthocyanins in the vacuole (Pourcel et al, 2010), chlorophagy of physiological and damaged chloroplasts (Izumi et al, 2017), reticulophagy (Liu et al, 2012), pexophagy (Shibata et al, 2013), mitophagy (Li et al, 2014) and xenophagy (Hafren et al, 2017).…”
Section: Dual Role Of K63-linked Chains In Plant Endocytosismentioning
confidence: 86%
See 1 more Smart Citation
“…The ELC/AtVPS23A ESCRT-I component also binds Ub in vitro (Spitzer et al, 2006). Interestingly, ELC/ AtVPS23A and AtFYVE1 directly bind to the AtPYL4 abscisic acid (ABA) receptor and AtIRT1, two ubiquitinated endocytosed cargos (Barberon et al, 2014;Belda-Palazon et al, 2016;Yu et al, 2016). Consistently, genetic interference with ELC/AtVPS23A or AtFYVE1 expression yields ubiquitinated protein accumulation in (Zhou et al, 2013), sequestration of anthocyanins in the vacuole (Pourcel et al, 2010), chlorophagy of physiological and damaged chloroplasts (Izumi et al, 2017), reticulophagy (Liu et al, 2012), pexophagy (Shibata et al, 2013), mitophagy (Li et al, 2014) and xenophagy (Hafren et al, 2017).…”
Section: Dual Role Of K63-linked Chains In Plant Endocytosismentioning
confidence: 86%
“…The BR receptor AtBRI1 is indeed decorated with K63-linked chains in vivo, undergoes K63 polyUb-dependent New Phytologist endocytosis and the expression of a ubiquitination-defective BRI1 variant leads to BR hypersensitivity (Martins et al, 2015). Similarly, the plasma membrane-associated pool of AtPYR/AtPYL ABA receptors is subjected to ubiquitination at the plasma membrane by the AtRSL1 RING E3 ligase and ESCRT-dependent endocytic sorting (Bueso et al, 2014;Belda-Palazon et al, 2016;Yu et al, 2016). Consistently, Arabidopsis fyve1 and vps23 mutants show stabilization of the AtPYL4 ABA receptor and are hypersensitive to ABA.…”
Section: Role Of K63-linked Ub Chains In Translationmentioning
confidence: 99%
“…So far, two main types of negative feedback regulatory loops of ABA signalling have been identified: the ubiquitin‐mediated proteasomal degradation of ABA key central regulators and the expressional regulation of the key central regulators genes. E3 ligases such as KEG, DWA1, and DWA2 target ABF/AREB/ABI5‐type bZIP transcription factors for proteasomal degradation (Chen, Liu, Stone, & Callis, ; Lee, Kang, et al, ; Liu & Stone, , ; Stone, Williams, Farmer, Vierstra, & Callis, ), whereas E2 ligase VPS23A and E3 ligases CUL4 and RSL1 promote the proteasomal degradation of PYR/PYL/RCABR receptors (Belda‐Palazon et al, ; Bueso et al, ; Seo et al, ; Yu et al, ). E3 ligases PUB12 and PUB13 target PP2C proteins, but only when they interact with ABA receptors (Kong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane‐localized auxin efflux carrier PIN2 (Spitzer et al ) and Brassinosteroid receptor BRI1 (Martins et al ) have been reported to be PVC cargo proteins, and are sorted for vacuolar degradation by the ESCRT system. Although the ESCRT pathway has long been considered specifically to be targeting integral membrane proteins, recent studies have demonstrated that non‐integral membrane proteins, such as the Arabidopsis ABA receptor PYR1‐LIKE 4 (PYL4), also employ ESCRT machinery components FYVE1 and VPS23A for endosomal sorting (Belda‐Palazon et al ; Yu et al ).…”
Section: Introductionmentioning
confidence: 99%